Evaluation of direct formic acid fuel cells with catalyst layers coated by electrospray - Kwon, Yongchai; Baek, Seungmin; Kwon, Byungwan; Kim, Jinsoo; Han, Jonghee (KOREAN INSTITUTE CHEMICAL ENGINEERS, 2010)
We investigated cell performance and performed phenomenological analyses of direct formic acid fuel cells (DFAFCs) incorporating anode (palladium) and cathode (platinum) catalysts prepared using a new electrospray coating technique. To optimize the design of the DFAFC, we examined the cell performance by the Pd catalyst loading and formic acid feed rate. Of Pd catalyst loaded samples, 3 mg/cm(2) sample showed the highest electrical performance with formic acid feed rate of 5 ml/min. This behavior was caused by discrepancies in the mass transfer limitation. When the feed rate was greater than 10 mL/min, however, the 7 mg/cm(2) sample provided the highest electrical performance, which was attributed to enhanced electrooxidation reactions. For comparison of the effect of the catalyst coating method on the cell performance of DFAFC, polarization curves of the DFAFC incorporating catalysts prepared using a conventional airspray coating method were also measured. As a result of the comparison, the electrospray coatingused DFAFC showed better cell performance. Based on these results, the cell performance of the DFAFCs was optimized when the catalysts using the electrospray catalyst coating were employed, the amount of Pd loaded on the anode electrode was 3 mg/cm(2) (Pd thickness: similar to 6 mu m), and the formic acid feed rate was 10 mL/min.
Keywords: ELECTROCHEMICAL IMPEDANCE; METHANOL ELECTROOXIDATION; PEMFC ELECTRODES; PERFORMANCE; OXIDATION; H-2/CO; PTAU